How to shine at work [ - Dominguez, Linda R. (McGraw-Hill, 2003)
Mergers, acquisitions, downsizing, re-organizing, bankruptcies, ever-changing bosses, off-site managers and tough economies are the ingredients of today's tumultuous workplace. Navigating this environment is a truly challenging assignment - seizing on it as an opportunity to advance your career almost seems foolhardy. And yet with the right portfolio of strategies, that's just what you can do. Author Linda Dominguez provides readers with more than 100 strategies, techniques and tips that will help them take control of even the most out-of-control work situations. These include how to navigate through today's office politics, overcome obstacles, make choices, recognize options, manage change, be accountable, take smart chances, move forward, turn any situation around andmarket yourself to your boss, no matter how clueless he orshe is. How to Shine at Work will offer vivid examples of others who have successfully wrestled with the disruptionsof job changes, downsizing, or other shifts.; Situations the book will discuss include: - Dealing with ever-changing bosses - Marketing yourself to your superiors and peers - Peer-level and management-level office politics - Gaining visibility, even when you're in a remote office - Coping with difficult coworkers - Asking for a promotion and raise in any economy This book, specifically designed for professionals and executives, will include quotes of wisdom, side bar information, sound career coaching and advice, and a variety of worksheets and self-tests